Pelatihan Capacity Building Bagi Guru-Guru Bimbingan Konseling SMA/SMK di Kabupaten Kuantan Singingi - Zulfan Saam; Elni Yakub; Donal Donal; Dhina Yuliana; Ria Asmerry Jafra; Retni Pratiwi; Rosmayani Rosmayani (PELANTAR PRESS, 2023)
The Target Group In This Training Activity Is Teachers Of Bk Sma/Smk In Kuantan Singingi Regency. The Target Group Is 32 Bk Teachers. Community Service Activities Through Capacity Building Training Will Be Held On Wednesday, May 10, 2023. The Training Participants Were Bk Teachers In Kuantan Singingi District. The Main Activity Of This Capacity Building Training Is Outbound Activities. This Training Aims To Provide Skills To Bk Teachers On How To Build The Capacity Or Capability Of Students Through Activities Outside The Classroom Or In The Open Field By Using A Personality Development Approach Through Games Or Various Games. The Game Aims To Build And Improve Aspects Of Student Personality Such As Cooperation, Courage, Honesty, Patience, Expression Of Feelings, Emotional Control, And Positive Thinking As Well As Create Superior Strategies In Achieving Goals. Training Participants Can Already Understand The Concepts Of Capacity Building And The Importance Of Outbound Activities In The Context Of Fostering Student Personality. Capacity Building Training Through Out Bound Can Be Done As A Form Of Service In Developing Aspects Of Student Personality That Students Are Directly Involved In Games.